Meningkatkan Kemampuan Mengenal Warna pada Anak Melalui Batik Jumputan - Latifah Permatasari Fajrin; Ayu Nur Khoyimah (UIN Raden Mas Said Surakarta, 2020)
The problem in this study is that the ability to recognize children's colors has not yet developed. The purpose of this research is to improve the ability to recognize colors through batik jumputanin group A TK Mranggen 01 Village, Polokarto District, Sukoharjo Regency Academic Year 2019/2020. This research uses Classroom Action Research (PTK). This research was conducted from October 2019 to March 2020. This classroom action research was conducted in two cycles and carried out in four stages, namely planning, implementing, observing, and reflecting. The research data were taken using test, observation, interview and documentation techniques. The results showed that making batik jumputanwas proven to improve students' ability to recognize colors. The increase in the ability to recognize colors can be seen from each cycle. Pre-cycle conditions, the percentage of children's ability to recognize colors reached a percentage of 17%. In the first cycle it increased to 33.33. In cycle II, the ability to recognize children's colors increased by 75%. So it can be concluded that making batik jumputancan improve the ability to recognize colors.